2016
DOI: 10.17509/edusentris.v3i2.216
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Program Bimbingan Dan Konseling Kelompok Untuk Meningkatkan Regulasi Diri, Efikasi Diri, Dan Prestasi Akademik

Abstract: Penelitan ini bertujuan untuk menguji efektivitas program bimbingan dan konseling kelompok Penelitian ini menggunakan rancangan kuasi eksperimen dengan sampel peserta didik kelas delapan berprestasi akademik rendah di SMP Al-biruni Cerdas Mulia. Sampel yang berjumlah 27 orang dibagi dalam tiga kelompok secara random, yaitu kelompok kontrol, kelompok bimbingan akademik tentang keterampilan belajar (BKB), dan kelompok konseling kelompok yang dipadukan dengan bimbingan akademik tentang keterampilan belajar (KKBKB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…al. In their research, they used a quasi-experimental design to measure the effectiveness of a counseling and group counseling program to improve self-regulation in learning, academic selfefficacy, and academic achievement. In their study, they found that students with low academic achievement tended to have low self-regulation and academic self-efficacy characteristics, besides that the test results also found that group counseling and guidance programs were effective in improving selfregulation and self-efficacy which ultimately improved academic achievement students (Noviawati, Elvi, LN, & Nurihsan, 2016). Furthermore, there is also research on the effect of moral coaching by citizenship education teachers on student learning discipline conducted by Hasanah et.…”
Section: Introductionmentioning
confidence: 97%
“…al. In their research, they used a quasi-experimental design to measure the effectiveness of a counseling and group counseling program to improve self-regulation in learning, academic selfefficacy, and academic achievement. In their study, they found that students with low academic achievement tended to have low self-regulation and academic self-efficacy characteristics, besides that the test results also found that group counseling and guidance programs were effective in improving selfregulation and self-efficacy which ultimately improved academic achievement students (Noviawati, Elvi, LN, & Nurihsan, 2016). Furthermore, there is also research on the effect of moral coaching by citizenship education teachers on student learning discipline conducted by Hasanah et.…”
Section: Introductionmentioning
confidence: 97%